Ligand/additive/base-free C(sp(2))-H activation and isocyanide insertion in PEG-400: synthesis of indolizine/imidazoline-fused heterocycles - Kumar, K. Shiva; Rajesham, Bandari; Kumar, N. Praveen; Ramulu, Meesa Siddi; Dandela, Rambabu (ChemistrySelect, 2018)
A ligand/base/metal oxidant free Pd-catalyzed C(sp(2))-H activation, followed by isocyanide insertion to synthesize indolizine/imidazoline fused heterocyclics in PEG-400 as a recyclable solvent. The present transformation is greener and an efficient strategy using oxygen as external oxidant. The spectroscopic properties of selected indolizine/imidazoline fused heterocyclics were studied by UV-visible and fluorescence spectroscopy.